Dynamics of polycyclic aromatic hydrocarbons (PAHs) in surface sediments of Cochin estuary, India. Issue 2 (30th January 2017) - Ramzi, A.; Habeeb Rahman, K.; Gireeshkumar, T.R.; Balachandran, K.K.; Jacob, Chacko; Chandramohanakumar, N.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) showed significant seasonal dynamics in surface sediments of a tropical ecosystem (Cochin estuary, south west coast of India). Concentrations ranged from 304 to 5874 ngg − 1 in pre-monsoon, 493 to 14, 149 ngg − 1 in monsoon, and 194 to 10, 691 ngg − 1 in post-monsoon. The estuary was moderately contaminated with low molecular weight PAH fractions, which increased rapidly during the monsoon season indicating land/river runoff as the major transport pathway. The dominance of 2–3 ring fractions in the PAH indicated petrogenic and low temperature combustion processes as major sources, while the very low levels of 5–6 ring components indicated low contribution from pyrolytic sources. Low molecular weight fractions were higher in concentration than the Effective Range-Median (ERM) levels, whereas high molecular weight PAHs were lower than the Effective Range-Low values (ERL). Calculated carcinogenic toxicity equivalents (TEQ) values ranged from 1 to 971 ng g − 1 in the surface sediments. Highlights: Sources and contamination status of PAHs in sediments of Cochin estuary, India. ∑ PAHs ranged from 194 to 14, 149 ngg − 1 dry weight. The study revealed petrogenic and pyrogenic sources of PAHs. LMW PAHs increased several fold in monsoon posing sediment contamination. Carcinogenic PAHs were low and remained below the effective range low (ERL) values.